Numerical investigations on the viscoelastic-damage behaviors of RIVE-induced concrete. (1st February 2023) - Chen, F.; Gao, C.; Jin, L.; Du, X.; Bary, B.; Le Pape, Y.; Sanahuja, J.
Abstract: Due to the remarkable influence of aggregate characteristics on the mechanical behaviors of concrete materials, and in particular the microcracking development, complex aggregates shapes instead of widely used spherical-shape need to be considered in advanced numerical approaches. Apart from that, in numerical simulations, an extra consideration of the influences of concrete's heterogeneity on its softening behaviors is strongly recommended by the scientific community. In this context, the softening behaviors of concrete materials undergoing heterogeneous expansion in the aggregates due to fast neutron radiation were investigated in the present paper, and the influences of both aggregate shape and the heterogeneity of aggregate expansion were considered. According to the real shapes of aggregates, polygon-shaped aggregates with random orientation were placed into a 3D numerical concrete specimen, and a two-stage finite element (FE) approach allowing a coupled thermal–mechanical analysis was proposed. In the first stage, the temperature field evolves in time and the 3D concrete specimen was estimated. In the second stage, the temperature- and neutron fluence-dependent heterogeneous expansion in the aggregates was calculated and introduced into the 3D mesoscopic model, and the development of microcracks in the concrete, the resulting mechanical responses, the loss in mechanical properties of the radiation-induced concrete was evaluated. Surmounting the limitations due to the spherical-shape of aggregate and the homogeneous assumption of the aggregate expansion in the concrete, the present paper developed a new methodology in which the combined effects of aggregate's shape and the heterogeneous distribution of aggregate expansion on the mechanical properties of radiation-induced concrete were considered, permitting evaluating the changes in the dimensional and mechanical properties of radiation-induced concrete. The proposed model provides a reference to assess the long-term durability and the structural integrity of nuclear power plants. Graphical abstract: Highlights: A thermal–mechanical 3D numerical model for concrete deterioration was established. Influence of aggregate characteristics on the mechanical behavior of concrete was investigated. Heterogeneous volume expansion evolution in the aggregates was accounted for. Crack propagation and non-linear mechanical responses of irradiated concrete were simulated. Residual mechanical properties of concrete irradiated by fast neutron were investigated.